Labor Skills and Foreign Investment in a Dynamic Economy: Estimating the Knowledge‐capital Model for Singapore. Issue 4 (17th October 2013) - Chellaraj, Gnanaraj; Maskus, Keith E.; Mattoo, Aaditya
Abstract Singapore is an interesting example of how the pattern of foreign investment changes with economic development. This paper studies inbound and outbound investment between Singapore and a sample of industrialized and developing countries over the period 1984–2007. Singapore's investments from industrialized nations shifted into skill‐seeking activities, while its investments in developing countries became concentrated in labor‐seeking production. The knowledge‐capital model is used to analyze the determinants of these shifts. The estimates suggest that a 10% increase in Singapore's skill differences with developing countries resulted in a 15.2% increase in outbound stocks of investment to the average recipient nation. A 10% decline in skill differences with industrialized countries after 1995 resulted in a 3.6% increase in inbound stocks from the average parent nation.